A TAPESTRY OF TIME: KIZIL GROTTOES AND THEIR CHINESE HERITAGE - Ming-Hua, Li; Xin-Yu , Wu (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
This paper presents a design of cultural and creative products based on the Kizil Grottoes. The design extracts the main elements of the Kizil Grottoes, such as the Flying Heaven, and combines them with various patterns in the grottoes. It also extracts the Buddha statues, decorative elements and colors from the Kizil Grottoes art, and recreates a series of representative elements by independent processing. The modern design language is incorporated into the design, and the cultural and creative products are applied to them. The design will explore the cultural and artistic value of the Kizil Grottoes to a greater extent, integrate practicality into the design and reflect regional and ethnic cultural characteristics. It will also strengthen the dissemination of the cultural and artistic glory of the Kizil Grottoes with cultural and creative products that have authentic and extensive cultural heritage